The UK Coronavirus Job Retention Scheme and smoking, alcohol consumption and vaping during the COVID-19 pandemic: evidence from eight longitudinal population surveys - Michael J. Green; Jane Maddock; Giorgio Di Gessa; Bożena Wielgoszewska; Sam Parsons; Gareth J. Griffith; Jazz Croft; Anna J. Stevenson; Charlotte F. Huggins; Charlotte Booth; Jacques Wels; Richard J. Silverwood; et al. (BMC Medicine, 2022)
Abstract Background Employment disruptions can impact smoking and alcohol consumption. During the COVID-19 pandemic, many countries implemented furlough schemes to prevent job loss. We examine how furlough was associated with smoking, vaping and alcohol consumption in the UK. Methods Data from 27,841 participants in eight UK adult longitudinal surveys were analysed. Participants self-reported employment status and current smoking, current vaping and alcohol consumption (>4 days/week or 5+ drinks per typical occasion) both before and during the early stages of the pandemic (April–July 2020). Risk ratios were estimated within each study using modified Poisson regression, adjusting for a range of potential confounders, including pre-pandemic behaviour. Findings were synthesised using random effects meta-analysis. Results Compared to stable employment and after adjustment for pre-pandemic characteristics, furlough was not associated with smoking (ARR = 1.05; 95% CI: 0.95–1.16; I 2: 10%), vaping (ARR = 0.89; 95% CI: 0.74–1.08; I 2: 0%) or drinking (ARR = 1.03; 95% CI: 0.94–1.13; I 2: 48%). There were similar findings for no longer being employed, and stable unemployment, though this varied by sex: stable unemployment was associated with smoking for women (ARR = 1.35; 95% CI: 1.00–1.82; I 2: 47%) but not men (0.84; 95% CI: 0.67–1.05; I 2: 0%). No longer being employed was associated with vaping among women (ARR = 2.74; 95% CI: 1.59–4.72; I 2: 0%) but not men (ARR = 1.25; 95% CI: 0.83–1.87; I 2: 0%). Conclusions We found no clear evidence of furlough or unemployment having adverse impacts on smoking, vaping or drinking behaviours during the early stages of the COVID-19 pandemic in the UK. Differences in risk compared to those who remained employed were largely explained by pre-pandemic characteristics.